The Role of Islamic Social Media Etiquette in Shaping Students’ Online Behavior: A Case Study of Eighth-Grade MTs Students - Adawiyah, Robiatal; Arifin, Moch. Bahak Udin By (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2025)
The widespread use of social media in Indonesia has significantly influenced student behavior, making it necessary to examine how religious-based social media etiquette can foster positive character development. This study explores the implementation of Islamic teachings on social media manners among eighth-grade students at MTS Bustanul Ulum, focusing on how these teachings shape their daily online behavior. Using a qualitative field research approach, the data are collected through observations and structured interviews with students and Islamic education teachers. The findings reveal that although students demonstrate a good understanding of the principles of social media etiquette—including tabayyun (fact-checking), respectful communication, and avoiding offensive content—there remains a gap between their knowledge and actual practice. Instances of cyberbullying and the use of inappropriate language persist across platforms such as Instagram and WhatsApp. These findings suggest that while instructional materials from the Aqidah Akhlaq curriculum are aligned with Islamic values, their internalization among students requires continuous support. The study implies that schools and families must actively guide students to apply Islamic manners consistently in digital interactions. This research contributes to the discourse on digital ethics in Islamic education and offers practical insights into character education in the digital era.